The Role of Higher Education Institutions in the Promotion of Students Entrepreneurship Skills: An Empirical Example - Paula LOUREIRO; Isabel FERREIRA; Teresa DIEGUEZ (Communications of International Proceedings, 2021)
Society lives periods of change coming from the ongoing digital transformation. In this context, several questions arise: What consequences will technological developments have on employment, security, privacy and democracy itself? What implications will they have on the nature and distribution of work among all and throughout life and, for each one, in their relationship with leisure? How to preserve and implement ethical principles related to its numerous social and economic implications? We are dealing with issues that do not address only education, but also too much more general effects on society. Nevertheless, on education they are special relevant, as education is a privileged instrument to guide change. Changes create instability and uncertainty, but also arises new possibilities, challenges, perspectives, and solutions. How can Higher Education respond to these challenges in this context? What teaching models can they implement? What teaching, learning and research strategies can be developed to answer the set of emerging skills? The purpose of this article is to promote a reflection on the role that Higher Education Institutions should play near students, specifically in the promotion of social entrepreneurship. It is presented a project of digital competencies, developed with students through volunteering, among local and national partners’ network and directed to communities inserted in disadvantaged socioeconomic contexts. With this sample we intend to share an active methodology of teaching and learning of IPCA, a Portuguese Higher Education Institution that aims to contribute in a more complete and adjusted training to the challenges of the labour market.
Keywords: Competitiveness; Higher Education; skills; social entrepreneurship; society